Review on Design of Oil Subsea Pipeline in Kikeh Field, Malaysia - Junaidi, M.N.; Koto, J. (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2016)
The encourage and positive development of oil and gas project in Malaysia deep water sea has led to the exchange of the underwater exploration from the shallow water depth to deeper water depth. However, this changes have raises the issue on deep water challenges for the submarine pipeline design. Designing a subsea pipeline is a challenge task and the process requires a detailed study and assessment of relevant pipeline design consideration and pipeline failure criteria. “Design of Deep Water Oil Subsea Pipeline in Malaysian Seas” project discuss a number of issues that need to be taken into account when designing a deep water subsea pipeline for Malaysian waters, mainly related to the excessive external pressure on the pipeline. Problems of high external pressure will results in pipeline failure such as system collapse and propagation buckling of a pipeline. In addressing these issues, consideration towards pipeline wall thickness design is being taken and the design process of the pipeline will be made in accordance to DNV class rule. Apart from that, a case study related to existed oil and gas project in Malaysia has being carried out, where Kikeh Gas Pipeline project from Kikeh oil field was selected as a study subject. By referring to the case study, a decent subsea pipeline design will be carried out and analyze so that it can suite to operate for Malaysian deep water seas.